(untitled) (Applied Biological Research, 2016)
To assess the effect of ascorbic acid supplementation on physiological parameters in buffalo viz., changes in body weight, dry matter intake and reproductive performances, eighteen Swamp buffaloes were divided into three groups. One group was fed with normal diet and other two groups supplemented with 10 and 15 g ascorbic acid animal-1 day-1. The group supplemented with 15 g ascorbic acid animal-1 day-1 had significantly lower respiration rate, pulse rate and rectal temperature as compared to the group supplemented with 10 or 0 g ascorbic acid animal-1 day-1. The dry matter intake kg-1 body weight, DMI per kg W0.75 was not affected by cent of animals coming into oestrus, conception rate and number of services per conception improved at higher level of ascorbic acid supplementation. It may be concluded that dietary supplementation of ascorbic acid has favourable impact in maintaining the physiological parameters, body weight and improved reproductive traits of swamp buffaloes.